Peran Keputusan Pembelian Memediasi Hubungan Kualitas Pelayanan, Brand Image, dan Diskon terhadap Kepuasan Konsumen di Ramayana Sidoarjo - Wulandari, Sintiya Ayu; Yani, Muhammad; Nugroho, Tofan Tri (Universitas Batanghari Jambi, 2025)
The purpose of this study was to analyze the role of purchasing decisions mediating the relationship between service quality, brand image, and discounts on customer satisfaction at Ramayana Sidoarjo. The study was conducted using a quantitative approach, with a sample of 96 respondents of Ramayana Sidoarjo customers who live in Sidoarjo. The data analysis was carried out using the help of the PLS program. The results of the study indicate that service quality, price and security affect customer satisfaction. In addition, it was found that service quality, brand image and discounts affect purchase satisfaction through purchasing decisions. It was also found that purchase satisfaction affects purchasing decisions at Ramayana Sidoarjo. This means that purchasing decisions mediate the relationship between service quality, brand image, and discounts on consumer satisfaction.